Characterizing Ham and Loin Quality as Hot Carcass Weight Increases to an Average of 119 Kilograms - Anna C. Dilger; Annie B. Lerner; Bailey Harsh; Brandon Fields; David A. King; Dustin Boler; Elaine Richardson; Emily A. Rice; Hannah E. Price; Jason C Woodworth; Jessica E. Lowell; Joel M. DeRouchey; et al. (Meat and Muscle Biology, 2019)
The objective was to characterize ham and loin quality of carcasses ranging from 78 to 145 kg (average ∼119 kg). Hot carcass weight (HCW), back fat depth, and loin depth was measured on 666 carcasses. Loin pH, instrumental and visual color and iodine value of clear plate fat (all 3 layers) was measured on approximately 90% of the population. Quality measurements of the ham, 14 d aged loin and chop, and loin chop shear force (SSF) were evaluated on approximately 30% of the population. Myosin heavy chain fiber type determination was completed on 49 carcasses. Slopes of regression lines and coefficients of determination between HCW and quality traits were calculated using the REG procedure in SAS and considered significantly different from 0 at P ≤ 0.05. As HCW increased, loin depth (b1 = 0.2496, P < 0.0001), back fat depth (b1 = 0.1374, P < 0.0001), loin weight (b1 = 0.0345, P < 0.0001), and ham weight (b1 = 0.1044, P < 0.0001) increased. Estimated lean (b1 = –0.0751, P < 0.0001) and iodine value (b1 = –0.0922, P < 0.0001) decreased as HCW increased, where HCW accounted for 24% (R2 = 0.24) of the variation in estimated lean and 7% (R2 = 0.07) of the variation in iodine value. However, HCW did not explain variation in ham quality traits (P > 0.15) and did not explain more than 1% (R2 ≤ 0.01) of the variation in 1 d loin color or pH. Loins from heavier carcasses were more tender (decreased SSF; b1 = –0.0674, P < 0.0001), although HCW only explained 9% of the variation in SSF. Hot carcass weight did not alter (P > 0.22) muscle fiber type percentage or area. These results suggest that increasing HCW to an average of 119 kg did not compromise pork quality.